CONTENT OF SUBJECTS OF THE AESTHETIC CYCLE OF THE MAIN NEVER AS A MEANS OF AESTHETIC EDUCATION VALUES OF SCHOOLCHILDREN (Pedagogy of Higher and Secondary Education, 2002)
The article pays attention to the artistic education of schoolchildren, by the means of art, as well as to the analysis of subjects of aesthetic cycle. (literature, music, and art).